The Drosophila Duox maturation factor is a key component of a positive feedback loop that sustains regeneration signaling. - Khan, S.J.; Abidi, S.N.F.; Skinner, A.; Tian, Y.; Smith-Bolton, R.K. (PLoS Genetics, 2017)
Regenerating tissue must initiate the signaling that drives regenerative growth, and sustain that signaling long enough for regeneration to complete. How these key signals are sustained is unclear. To gain a comprehensive view of the changes in gene expression that occur during regeneration, we performed whole-genome mRNAseq of actively regenerating tissue from damaged Drosophila wing imaginal discs. We used genetic tools to ablate the wing primordium to induce regeneration, and carried out transcriptional profiling of the regeneration blastema by fluorescently labeling and sorting the blastema cells, thus identifying differentially expressed genes. Importantly, by using genetic mutants of several of these differentially expressed genes we have confirmed that they have roles in regeneration. Using this approach, we show that high expression of the gene moladietz (mol), which encodes the Duox-maturation factor NIP, is required during regeneration to produce reactive oxygen species (ROS), which in turn sustain JNK signaling during regeneration. We also show that JNK signaling upregulates mol expression, thereby activating a positive feedback signal that ensures the prolonged JNK activation required for regenerative growth. Thus, by whole-genome transcriptional profiling of regenerating tissue we have identified a positive feedback loop that regulates the extent of regenerative growth.